2016
DOI: 10.1016/j.abb.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore formation process in artificial cell membrane induced by plasma-generated reactive oxygen species

Abstract: We investigated morphological change of an artificial lipid bilayer membrane induced by oxygen radicals which were generated by non-equilibrium atmospheric pressure plasma. Neutral oxygen species, O((3)Pj) and O2((1)Δg), were irradiated of a supported lipid bilayer existing under a buffer solution at various conditions of dose time and distances, at which the dose amounts of the oxygen species were calculated quantitatively. Observation using an atomic force microscope and a fluorescence microscope revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 72 publications
2
26
0
1
Order By: Relevance
“…It was suggested, that via bond flipping mechanism the · OH radical might reach into the bulk of liquids 92 , allowing the attack on the lipid. In addition, sub-stoichiometric amounts are assumed sufficient to start a radical chain reaction 93 , leading to the observed oxidation pattern. Furthermore, the distance of 1.8 cm between the gas–liquid interface and the lipid bilayer could be a reason for a different effect on the lipid bilayer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested, that via bond flipping mechanism the · OH radical might reach into the bulk of liquids 92 , allowing the attack on the lipid. In addition, sub-stoichiometric amounts are assumed sufficient to start a radical chain reaction 93 , leading to the observed oxidation pattern. Furthermore, the distance of 1.8 cm between the gas–liquid interface and the lipid bilayer could be a reason for a different effect on the lipid bilayer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, in a computational simulation study, Yusupov et al has shown that the synergistic action of electric field with H 2 O 2 potentially increases phospholipid membrane permeability that increases the ingress of RONS into cells [54]. This perhaps occurs on a very fast time-scale with only small nanometre diameter pore openings in the phospholipid membrane [99]. This would explain only minimal leakage of the encapsulated CF from the vesicles with plasma jet treatment.…”
Section: Discussionmentioning
confidence: 97%
“…[ 132 ] (j) CAP‐generated nanopore on the cell membrane (the zoomed‐in picture captures the edge of the nanopores had clear contrast compared with the flat supported lipid bilayers (SLB). [ 133 ] (k) The intracellular ROS after CAP treatment measured by flow cytometry analysis. [ 134 ] CAP, cold atmospheric pressure plasma; RONS, reactive oxygen/nitrogen species…”
Section: Transport Of Reactive Agentsmentioning
confidence: 99%
“…[ 154 ] Observation using an atomic force microscope and a fluorescence microscope revealed that the dose of the ROS generated nanopores with a diameter of 10–50 nm in a phospholipid bilayer, and finally destructed the bilayer structure (Figure 5j). [ 133 ]…”
Section: Transport Of Reactive Agentsmentioning
confidence: 99%